Comparative analysis of biometrical and reproductive indices, proximate composition, and hemato-biochemical variables of cuchia eel Monopterus cuchia (Hamilton, 1822) from six different localities of Bangladesh - Nandi, Shishir Kumar; Al Mamun, Md Abdullah; Suma, Afrina Yeasmin; Abdul Kari, Zulhisyam; Wei, Lee Seong; Tahiluddin, Albaris B.; Manjappa, Nesara Kadadakatte; Nasren, Shamima; Saha, Shuva; Téllez-Isaías, Guillermo; Bottje, Walter G.; Kabir, Muhammad Anamul (Elsevier BV, 2024)
Cuchia eel (Monopterus cuchia) is among the most sought-after freshwater fish, owing to its exceptional nutritional profile and high consumer demand. The current research aimed to establish baseline data by comparing the proximate composition, hematological, and plasma biochemical indices of Cuchia eel populations across six different geographical locations in Bangladesh: Bogra, Haluaghat, Jamalpur, Moktagacha, Sylhet, and Tangail. By examining these parameters, we aim to gain valuable insights into the nutritional benefits, physiological responses, and potential adaptations of this species to varying environments. The statistical analysis revealed no significant (P > 0.05) variances in the whole-body proximate composition of the fish captured from distinct areas. However, it was observed that different geographical regions had remarkable impacts on the variations of the majority of the hematological parameters, except for some cases. Additionally, there was a notable (P < 0.05) increase or decrease in most of the serum biochemical contents in certain localities as compared to others in this study. Light microscopic examination of Cuchia eel blood smears exhibited lower numbers but larger sizes of RBCs. The findings of this study lead to the conclusion that different localities had significant impacts on the hematology and blood biochemical indices of Cuchia eel, even though the whole-body proximate composition showed no significant variations. This research contributes to a deeper understanding of the physiological aspects of Cuchia eel.
Keywords: Social sciences (General); H1-99; Proximate composition; Q1-390; Science (General); Hematology; Plasma biochemistry; Cuchia eel; Research Article; 14. Life underwater